A New Bacterial Adenosine‐Derived Nucleoside as an Example of RNA Modification Damage. Issue 11 (7th February 2023) - Bessler, Larissa; Vogt, Lea‐Marie; Lander, Marc; Dal Magro, Christina; Keller, Patrick; Kühlborn, Jonas; Kampf, Christopher J.; Opatz, Till; Helm, Mark
Abstract: The fields of RNA modification and RNA damage both exhibit a plethora of non‐canonical nucleoside structures. While RNA modifications have evolved to improve RNA function, the term RNA damage implies detrimental effects. Based on stable isotope labelling and mass spectrometry, we report the identification and characterisation of 2‐methylthio‐1, N 6‐ethenoadenosine (ms 2 ϵA), which is related to 1, N 6‐ethenoadenine, a lesion resulting from exposure of nucleic acids to alkylating chemicals in vivo. In contrast, a sophisticated isoprene labelling scheme revealed that ms 2 ϵA biogenesis involves cleavage of a prenyl moiety in the known transfer RNA (tRNA) modification 2‐methylthio‐ N 6‐isopentenyladenosine (ms 2 i 6 A). The relative abundance of ms 2 ϵA in tRNAs from translating ribosomes suggests reduced function in comparison to its parent RNA modification, establishing the nature of the new structure in a newly perceived overlap of the two previously separate fields, namely an RNA modification damage. Abstract : Tandem mass spectrometry combined with stable isotope labelling identified a new nucleoside species, namely 2‐methylthio‐1, N 6‐ethenoadenosine (ms 2 ϵA), in bacterial transfer RNA (tRNA). Its rare occurrence on tRNA, especially when involved in translation, and the structural as well as metabolic relation to the known tRNA modification 2‐methylthio‐ N 6‐isopentenyladenosine (ms 2 i 6 A) argue for ms 2 ϵA to be an oxidatively damaged form of ms 2 i 6 A.